The mechanisms of translation of English new terms into Ukrainian (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article focuses on the conditions and ways of translating new terms of the English language into Ukrainian. Taking into account the communicative and functional peculiarities of translating new terms, this article develops a typology of translating general technical neologisms.
Keywords: translation; scientific and the technical of terms; neologisms; mechanisms